Durabilitas Campuran AB-BC Yang Menggunakan Batu Sungai Lawaoo Kecamatan Lalabata Kabupaten Soppeng - Hendra Pabisa; Alpius; Monika D.M Palinggi (Paulus Civil Engineering Journal, 2022)
In bending pavements, it is necessary to know the level of durability of a concrete asphalt mixture against its durability value, for example, it is often seen in road pavements now the level of durability or durability value is minimal this is due to factors from weather such as rain, then the pavement becomes easily cracked. Therefore, the Lawaoo River stone is used in Lalabata District, which is one of the rivers in Soppeng Regency, which functions as material collection in soppeng regency itself. The use of this material is used by local communities as building construction materials because the material is used more efficiently in terms of cost.The test method carried out is the Marshall test with the intention of obtaining the Stability and Flow values used to obtain the Durability value. The average durability value at each 12-hour soaking; 24 hours; 36 hours; 48 hours; and 60 hours is 97.59%-84.70%. In terms of soaking results, it is concluded that the lowest AC-BC mixed test object from 12 hours to 36 hours is still at the durability value limit (97.59%-90.00%) and 48 hours to 60 hours has passed the minimum durability value limit (89.99%-84.70%).